Final Year Nursing Students' Knowledge and Attitudes regarding Children's Pain. (14th February 2020) - Kusi Amponsah, Abigail; Kyei-Dompim, Joana; Kyei, Evans Frimpong; Oduro, Evans; Afaya, Richard Adongo; Ahoto, Collins Kwadwo
Abstract : Pain is one of the commonest reasons why children visit the hospital. Inadequately treated pain in children can negatively affect their physical, psychological, and social well-being; it also places financial burden on families of affected children and healthcare systems in general. Considering the eventual suffering of vulnerable children and their families if nursing students are insufficiently educated and ill-prepared, the current study aimed at assessing final year nursing student's knowledge and attitudes pertaining to pediatric pain. A descriptive cross-sectional study was conducted among 100 final year undergraduate nursing students at a private university college in Ghana. In addition to their ages and gender, the students responded to the 42 individual items on the Pediatric Nurses' Knowledge and Attitudes Survey regarding pain (PNKAS) instrument. Descriptive statistical analysis was aided by the Statistical Package for Social Sciences version 25 software. The mean age of the final year nursing students was 29 years (range of 21 to 47 years); a majority of them were females (78%). Participants had an average (SD) correct answer score of 44.0% (10.6%). Good pediatric pain knowledge and attitudes were observed in items that were related to the individualized and multidimensional nature of the pain experience and its treatment, benefits of pre-emptive analgesia, pharmacodynamics, and pain assessment. Poor pediatric pain knowledge and attitudes occurred in items that focused on pain perceptions, opioid drug administration, useful pain medications, pain physiology, and nonpharmacological pain management interventions. Final year nursing students have insufficient knowledge and attitudes toward children's pain management. Areas of good and poor pediatric pain knowledge and attitudes should be considered when designing and implementing educational interventions on this subject. Curricular revisions should be made on existing nursing curriculum to lay more emphasis on children's pain management and use educational interventions that support knowledge translation for improved care.